RIT1 deficiency alters cerebral lipid metabolism and reduces white matter tract oligodendrocytes and conduction velocities - Lei Wu; Fang Wang; Carole L. Moncman; Mritunjay Pandey; Harrison A. Clarke; Hilaree N. Frazier; Lyndsay E.A. Young; Matthew S. Gentry; Weikang Cai; Olivier Thibault; Ramon C. Sun; Douglas A. Andres (Heliyon, 2023)
Oligodendrocytes (OLs) generate lipid-rich myelin membranes that wrap axons to enable efficient transmission of electrical impulses. Using a RIT1 knockout mouse model and in situ high-resolution matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) coupled with MS-based lipidomic analysis to determine the contribution of RIT1 to lipid homeostasis. Here, we report that RIT1 loss is associated with altered lipid levels in the central nervous system (CNS), including myelin-associated lipids within the corpus callosum (CC). Perturbed lipid metabolism was correlated with reduced numbers of OLs, but increased numbers of GFAP+ glia, in the CC, but not in grey matter. This was accompanied by reduced myelin protein expression and axonal conduction deficits. Behavioral analyses revealed significant changes in voluntary locomotor activity and anxiety-like behavior in RIT1KO mice. Together, these data reveal an unexpected role for RIT1 in the regulation of cerebral lipid metabolism, which coincide with altered white matter tract oligodendrocyte levels, reduced axonal conduction velocity, and behavioral abnormalities in the CNS.